Youth Heterotopias in Precarious Times: The Students Autonomous Collectivity. (February 2016) - Pechtelidis, Yannis
Under the structural restraints of the current financial, social and political crisis, I examine the case of a collectivity of students in Greece as an alternative small-scale form of political and cultural action, and I explore its dynamics and limits. I claim that the 'collectivity' is a form of heterotopia, that is, a specific social and cultural space, which somehow reflects and at the same time distorts, unsettles or inverts other spaces. In particular, I seek to uncover the rituals, practices and mentalities produced by the participants of this youth cultural space, and to understand how new subjectivities and collectivities come into being. In this context, I discuss some of the relevant literature on youth political participation. Furthermore, I illustrate the debate about 'autonomy' and 'hegemony' within social and political theory today.